From percentage to prediction - Mona Blåsjö (Ibérica, 2011)
A less-frequently discussed parallel-linguistic issue is the parallel language of visuals and numerals: the diagrams, tables, models, mathematical signs and different symbols that students have to deal with in their reading and writing. Texts are multimodal, that is they are constructed with visual objects and different sign systems as well as writing. For new students, it can be difficult to grasp how visuals and numerals can have different meanings in different contexts, such as academic disciplines. For teachers, the disciplinary use of the visuals and numerals is often so ingrained that they may have difficulty seeing the problems that students face. Drawing on the theoretical framework of social semiotics and the neo-Vygotskian perspective, this article shows how new students of economics in Sweden encounter a multimodal academic literacy. The article also discusses some of the difficulties relating to this situation and argues for a raised awareness among teachers in order to scaffold students into academic, visual literacies.